Nexus of Capital Structure and Firm Value in SSA Insurance Companies; The Moderating Effect of Intellectual Capital - Msomi, Thabiso Sthembiso; Olarewaju, Odunayo Magret; Sibanda, Mabutho (Journal of Ecohumanism, 2025)
This study examined the nexus between capital structure and firm value in Sub-Saharan African insurance companies, emphasizing the moderating effect of intellectual capital. The study assessed how leverage indicators, including the debt-to-equity ratio, short-term debt, and long-term debt, impacted firm value measured by Tobin’s Q, while also examining how intellectual capital enhanced the relationship between these capital structure elements and firm performance. A dynamic panel two-step system Generalized Method of Moments estimation was utilized to analyze a sample of 122 insurance companies from 46 Sub-Saharan African countries, covering the period from 2010 to 2022. The study assessed the influence of various leverage indicators on firm value, measured by Tobin’s Q, and examined how intellectual capital moderates these relationships. The findings revealed that intellectual capital positively affected firm value and significantly moderated the impact of capital structure on performance. Specifically, companies with higher levels of intellectual capital exhibited a more favorable relationship between capital structure and performance. Additionally, while short-term and excessive leverage negatively impacted firm value, long-term debt and firm size were associated with improved performance. This study contributed valuable insights into the role of intellectual capital in the insurance sector, suggesting that policymakers and industry leaders should prioritize intellectual capital development and prudent debt management to enhance firm resilience and long-term value.